Hedges and safe havens: An examination of stocks, gold and silver in Latin America’s stock market - Dias, Rui; Carvalho, Luísa Cagica (Revista de Administração da UFSM, 2020)
Purpose - This essay aims to analyze whether gold (Gold Bullion: Zurich) and silver (Silver Paris Spot E/KG) will be a safe haven for diversifying portfolios in Latin America's stock markets. Design/methodology/approach - The analyzed data are the price indexes of the stock markets of Argentina (S&P Merval), Brazil (Ibovespa), Chile (S&P/CLX IGPA), Peru (S&P/BVL General IGBL), Mexico (IPC), USA (Dow Jones), gold (Gold Bullion: Zurich), and silver (Silver Paris Spot E/KG), from December 31, 2019 to September 2, 2020. To answer the research question we used Gregory and Hansen’s methodology (1996), and the VAR Granger causality/block exogeneity Wald tests model. Findings - The results indicate that the markets have very significant integrations and causalities, that is, gold and silver do not function as safe havens for the diversification of portfolios in Latin American stock markets. Research limitations/implications - While the present investigation used general indices, in future studies sectoral indices can be used, as well as intraday data to have more robust evidence regarding the diversification of portfolios in these regional markets. Originality/value - This investigation differs from previous studies because it focuses on the rebalancing of portfolios through the estimation of integration models and shocks between gold and silver and the Latin American markets. This differs from the previous ones, which analyzed the average dependencies between gold and financial market movements, and between gold and currency depreciation.